Efeito das Ações de Marketing na Escola sobre o Comportamento de Consumo - Afonso, Ana (2022)
Our study aims to analyze the effect of marketing actions in schools, driven by health-food companies, on the consumption behavior of students to understand whether they (a) show higher preference for healthy food and drinks; (b) choose to take such goods home; are aware that consuming these goods is a healthy habit; and (c) realize that sales of the companies that produce such health foods and drinks improve. We wish to contribute to the literature by using an experimental exercise in three schools in Porto district, Portugal. Our sample included 307 students aged from 6 to 16 years old, with 153(154) students belonging to the experimental (control) group. The regression results confirm our hypotheses. In particular, we found that the level of education of parents did not seem to have an impact, the results across male and female students are very close and that students’ age did not affect the results between groups, but did affect score values.